High‐resolution magnetics reveal the deep structure of a volcanic‐arc‐related basalt‐hosted hydrothermal site (Palinuro, Tyrrhenian Sea). (26th June 2015) - Szitkar, Florent; Petersen, Sven; Caratori Tontini, Fabio; Cocchi, Luca
Abstract High‐resolution magnetic surveys have been acquired over the partially sedimented Palinuro massive sulfide deposits in the Aeolian volcanic arc, Tyrrhenian Sea. Surveys flown close to the seafloor using an autonomous underwater vehicle (AUV) show that the volcanic‐arc‐related basalt‐hosted hydrothermal site is associated with zones of lower magnetization. This observation reflects the alteration of basalt affected by hydrothermal circulation and/or the progressive accumulation of a nonmagnetic deposit made of hydrothermal and volcaniclastic material and/or a thermal demagnetization of titanomagnetite due to the upwelling of hot fluids. To discriminate among these inferences, estimate the shape of the nonmagnetic deposit and the characteristics of the underlying altered area—the stockwork—we use high‐resolution vector magnetic data acquired by the AUV Abyss (GEOMAR) above a crater‐shaped depression hosting a weakly active hydrothermal site. Our study unveils a relatively small nonmagnetic deposit accumulated at the bottom of the depression and locked between the surrounding volcanic cones. Thermal demagnetization is unlikely but the stockwork extends beyond the limits of the nonmagnetic deposit, forming lobe‐shaped zones believed to be a consequence of older volcanic episodes having contributed in generating the cones.